2
$\begingroup$

Let $V$ and $U$ be two finite-dimensional vector spaces of dimensions $n$ and $m$ respectively. For $f\in \mathrm{End}\,V$ we define a multilinear, anti-symmetric function: $$V\times ...\times V\to \Lambda^nV,~~(v_1, v_2,\dots, v_n)\mapsto fv_1\wedge fv_2\wedge\dots\wedge fv_n$$ what corresponds to a linear function $\det f\colon \Lambda^nV\to\Lambda^nV$.

Now I would like to prove that $\det f\oplus g = \det f\cdot \det g$ (i. e. the determinant of a block diagonal matrix is the product of the determinants of blocks).

Naively, if $v_1, \dots, v_n$ and $u_1,\dots, u_m$ are bases of $V$ and $U$, we merge them into a basis of $V\oplus U$ and: $$ (f\oplus g)v_1\wedge \dots (f\oplus g)v_n\wedge (f\oplus g)u_1\wedge (f\oplus g)u_m = \\=(fv_1\wedge \dots\wedge fv_n) \wedge (gu_1\wedge\dots\wedge g u_m) =\\ =\det f\cdot \det g \cdot v_1\wedge\dots\wedge v_n \wedge u_1\wedge\dots\wedge u_m$$ However, I can't bracket out these two terms without some kind of identification between $\Lambda^{n+m}(V\oplus U)$ and pressumably $\Lambda^nV\otimes \Lambda^mU$. How does one fix this rigorously?

Edit: From Exterior power "commutes" with direct sum we know that there is an isomorphism $\Lambda ^{n+m}(V\oplus U) \simeq \Lambda^nV\otimes \Lambda^mU$.

$\endgroup$
2
$\begingroup$

Let $i_V\colon V\to V\oplus U$ and $i_U\colon U \to V\oplus U$ be the two inclusions. Now if $v_1, \dots, v_n$ is a basis of $V$ and $u_1,\dots, u_m$ is a basis of $U$, then: $$i_Vv_1, \dots, i_Vv_n, i_Uu_1, \dots, i_Uu_m$$ is a basis of $V\oplus U$. From the definition of $f\oplus g$ we know that $(f\oplus g)i_Vv_i=i_Vfv_i$ and $(f\oplus g)i_Uu_i=i_Ugu_i$. Now define: $$x := (f\oplus g)i_Vv_1\wedge \dots\wedge (f\oplus g)i_Vv_n \wedge(f\oplus g)i_Uu_1\wedge\dots\wedge (f\oplus g)i_Uu_m = \\ =i_Vfv_1\wedge\dots\wedge i_Vfv_n\wedge i_Ugu_1\wedge\dots\wedge i_Ugu_m .$$

We have a linear isomorphism $\alpha\colon \Lambda^{n+m}(V\oplus U)\to \Lambda^nV\otimes \Lambda^mU$. Acting with it we get an expression: $$\alpha(x) = (fv_1\wedge\dots\wedge fv_n)\otimes(gu_1\wedge\dots\wedge gu_m) \\ = \det f\cdot \det g\cdot (v_1\wedge\dots \wedge v_n)\otimes (u_1\wedge\dots\wedge u_m)$$ Using its inverse: $$x=(\alpha^{-1}\alpha)(x) = \det f\cdot \det g\cdot i_Vv_1\wedge\dots\wedge i_Vv_n\wedge i_Uu_1\wedge\dots\wedge i_Uu_m ,$$ which proves the claim.

We can reduce clutter resulting from inclusions – the crucial step is to move the calculation from $\Lambda^{n+m}(V\oplus U)$ to $\Lambda^nV\otimes \Lambda^mU$, and then translate the results back.

$\endgroup$

Your Answer

By clicking “Post Your Answer”, you agree to our terms of service, privacy policy and cookie policy

Not the answer you're looking for? Browse other questions tagged or ask your own question.